1978
DOI: 10.1126/science.694537
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Macrophage Tumoricidal Function: A Role for Prostaglandins of the E Series

Abstract: Exogenously added prostaglandins E1 and E2, but not F2alpha, inhibited the tumoricidal activity of interferon-activated macrophages of mice. A role for adenosine 3',5'-monophosphate (cyclic AMP) in modulating macrophage functional activity was suggested because prostaglandins of the E series increase intracellular concentrations of cyclic AMP in macrophages and because treatment of interferon-activated macrophages with dibutyryl cyclic AMP consistently inhibits expression of cytotoxicity. Since the activated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

1980
1980
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(43 citation statements)
references
References 24 publications
3
39
0
1
Order By: Relevance
“…On the other hand, Plescia et al (1975) have suggested that PGs may be used by tumours to subvert the immune system. This hypothesis also accords with the marked sensitivity of lymphocytes as well as macrophages to PGE which, by increasing cyclic AMP levels, antagonizes mitogen-induced cell proliferation or cytotoxicity (Pelus & Strausser, 1977;Schultz et al, 1978).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…On the other hand, Plescia et al (1975) have suggested that PGs may be used by tumours to subvert the immune system. This hypothesis also accords with the marked sensitivity of lymphocytes as well as macrophages to PGE which, by increasing cyclic AMP levels, antagonizes mitogen-induced cell proliferation or cytotoxicity (Pelus & Strausser, 1977;Schultz et al, 1978).…”
mentioning
confidence: 54%
“…We consider more likely the hypothesis proposed by Plescia et al (1975) Tomasi et al, 1978Tomasi et al, , 1979Tomasi, 1976 (Pelus & Strausser, 1977;Schultz et al, 1978 (Karim, 1976). At present it is difficult…”
Section: Methodsmentioning
confidence: 99%
“…The specific action of the -series prostaglandins is noteworthy because the doses of PGE used in this study to increase penetration rates (60 µg/ml or 170 µ ) or elevate cAMP (16-8 µg/ml or 47 µ ) are severalfold higher than the 10µ dose of PGE normally used in biological experiments to achieve, for example, maximal suppression of macrophage function through the elevation of intracellular cAMP (O'Donnell, 1974;Schultz, Pavlidis, Stylos & Chirigos, 1978;Taffet, Pace & Russell, 1981). Nevertheless, the doses of prostaglandin employed in the present study are physiological in the sense that seminal plasma from normal fertile men may contain 2-272 µg PGE/ml and 53-1094 µg 19-hydroxy PGE/ml (Templeton, Cooper & Kelly, 1978) (Kanwar, Yanagimachi & Lopata, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Because prostaglandins are known to affect macrophage functions, namely cytotoxicity and TNF-␣ production [17,18], we tested the effect of PGE 2 on macrophage cytotoxic activity and on TNF and NO production. As shown in Figure 5, the addition of PGE 2 to the cocultures inhibited significantly the TNF release without affecting the release of NO nor macrophage cytotoxicity against mycoplasma-infected YAC-1 cells.…”
Section: Arginini Increases Macrophage Cytotoxicity To Yac-1 Cellsmentioning
confidence: 99%
“…In this study we further investigated the cytotoxic activity of macrophages induced by M. arginini by measuring NO and TNF release and the contribution of these molecules to the macrophage cytotoxic activity. We also investi-gated the effect of PGE 2 , which is known to down-regulate some macrophage activities [17,18], on the cytotoxic activity of thioglycollate-elicited macrophages and on the release of TNF and NO by these cells.…”
Section: Introductionmentioning
confidence: 99%